Role of a Urinary Biomarker in the Common Mechanism of Physical Performance and Cognitive Function - Jiang, Shan; Cui, Ju; Zhang, Li-Qun; Liu, Zhen; Zhang, Yan; Shi, Yuan; Cai, Jian-Ping (Frontiers in Medicine, 2022)
Introduction: Healthy aging is described as a process of developing and maintaining intrinsic abilities, including physical and cognitive functions. Although oxidative stress is a common mechanism shared by loss of muscle strength and dementia, its relationship with decreased physical performance and cognitive impairment remains unclear. We aimed to investigate the role of urinary 8-oxo-7, 8-dihydroguanosine (8-oxoGsn), a biomarker of oxidative damage to RNA, in physical and cognitive decline. Methods: The study followed a cross-sectional design and recruited 40–94-year-old inhabitants of Beijing, China (471 men and 881 women). The physical performance of the participants was assessed using handgrip strength, walking speed, and the repeated chair stand test. The cognitive function was assessed using the Montreal Cognitive Assessment (MoCA) 5-min protocol. Urinary 8-oxoGsn levels were measured for all participants. Results: Participants with high urinary 8-oxoGsn levels were more likely to have low grip strength, slow walking speed, poor performance in the repeated chair stand test, and low scores on the MoCA 5-min protocol (odds ratio [OR] 3.43, 95% confidence interval [CI]: 1.52–7.76; OR 1.71, 95% CI: 1.16–2.53; OR 2.06, 95% CI: 0.92–4.63; OR 1.75, 95% CI: 1.18–2.58), after adjusting for age, sex, smoking habits, alcohol use, hypertension, diabetes, and cerebro-cardiovascular disease, chronic kidney disease. Conclusion: Elevated levels of oxidative stress are independently associated with cognitive and physical impairment. Thus, these results can help in the early identification and development of strategies for the prevention and treatment of intrinsic capacity decline.